Malignant mesothelioma tumours: molecular pathogenesis, diagnosis, and therapies accompanying clinical studies - Sahu, Ram Kumar; Ruhi, Sakina; Jeppu, Ashok Kumar; Al-Goshae, Husni Ahmed; Syed, Ayesha; Nagdev, Sanjay; Widyowati, Retno; Ekasari, Wiwied; Khan, Jiyauddin; Bhattacharjee, Bedanta; Goyal, Manoj; Bhattacharya, Sankha; et al. (Frontiers in Oncology, 2023)
Malignant mesothelioma (MM) is a relatively uncommon and confrontational tumor that evolves in the peritoneum cavities and is highly resistant to standard treatments. Simian virus 40 (SV40), might have a role, despite asbestos exposure being the primary risk factor for lung cancer. Tumor suppressor gene loss is the main pattern of lesions in mesothelioma. Despite worldwide bans on asbestos manufacturing and supply, its prevalence continues to rise. It presents in a variety of ways and behaves in a variety of ways, making the diagnosis a challenge. The majority of current treatments available for MM are ineffective, with a median average life expectancy of 10 to 12 months. However, in recent years, significant progress has been made in the insight into the genetics and pathophysiology of mesothelioma. The genesis and progression of MM are related to many major genetic changes. This relates to NF2 and/or LATS2 mutations, activating the transcriptional co-activator YAP. In addition, it has exposed the limits of existing diagnostic algorithms and discovered novel therapeutic targets. There have been novel alternatives for treating related pleural effusions as well as the introduction of targeted treatments in recent clinical studies that have investigated the function of surgery. Mesothelioma care is becoming increasingly difficult due to the rising complexity of mesothelioma management and the urgent need for further research, making a multidisciplinary team structure vital. This article highlights the key findings of the molecular pathogenesis of mesothelioma with special emphasis on the management of mesothelioma.